Future health expenditures and its determinants in Latin America and the Caribbean: a multi-country projection study - Rao, Krishna D. (2024)
Summary Background Countries in Latin America and the Caribbean (LAC) have experienced important demographic, epidemiological, economic, and policy developments that raise concerns about their ability to afford health expenditures in the future. This paper forecasts how current health expenditures (CHE) in LAC countries will change over the next 30 years and identifies key drivers of health expenditure growth. Methods A statistical model to forecast CHE based on changing disease burden, economic growth, technology, and demography was developed. CHE by age and disease group at baseline (2018/19) were estimated for countries in the LAC region based on seven index countries. Baseline expenditures were projected to 2050. Findings Per capita CHE will increase across the LAC region (median increase 2.75 times) between baseline and 2050. All Latin American countries are expected to double per capita CHE in this period. Expected increases in Caribbean countries are more variable. Large increases in CHE growth related to neoplasms, circulatory system and genitourinary conditions are observed. Growth in CHE will be highest in older age groups. Interpretation Increases in health expenditures will be driven largely by economic growth and technology, while demography and epidemiology had smaller effects. The control of health expenditures and more efficient use of health resources must become a priority for the LAC region. Funding This study was funded by the Inter-American Development Bank.